Government support and the development of new quality productivity: a text mining analysis based on the provincial government work report - Sun, Weidong; Zhou, Yanchen; Li, Yanyu; Hui, Xiyu; Qiu, Yifan; Liu, Hongrong (Transactions on Economics, Business and Management Research, 2024)
The new quality productivity is an important driving force to push forward the Chinese modernization in our country, based on the text mining of 510 provincial government work reports from 2011 to 2023, this paper estimates the government's support for the development of new-quality productivity, and carries out the principal component analysis by constructing the index system of the development of new-quality productivity, this paper measures the development level of new quality productivity and empirically tests the mechanism of government support on the development of new quality productivity with panel data model. The empirical results show that government support has a positive effect on the performance of new qualitative productivity at the 5% significance level. Based on the research conclusion, the paper proposes that government agencies should understand the actual demand of new quality productivity development, strengthen the implementation of supply-side reform, focus on long-term development, and create a good innovation environment.